Factores que influyen a que el régimen laboral especial de la micro empresa no contribuye a generar trabajo decente en el distrito de Trujillo - Reyes Jimenez, Oswel Smith (2017)
SUMMARY Micro-enterprises are most throughout our country represent the largest number of jobs to citizens formally but mostly informally. Thus, the factors that influence the special labor regime microenterprise does not contribute to generate decent work in Trujillo , is necessary and appropriate determination, they confirmed that these are diverse and mostly are; tax, labor standards, labor costs, the informality and lack of productivity of enterprises. Decent Work that is worthy for a properly live in a society with his family person is a goal that every society must reach including the Peruvian specifically Trujillana within this research the main factors determined by the regime Laboral Special Micro Enterprise despite being differentiated mostly were not welcomed by existing entrepreneurs in Trujillo. Microenterprises investigated both their drivers and their workers in order to determine which conditions are to review their improvement and timely development. The state does not inspire confidence and incentives for microentrepreneurs are formalized. So also the administrative authority Regional Labor Management Labor and Employment Promotion of Freedom does not play its role in an appropriate way; added to that there is no culture of paying taxes and labor costs be high for microentrepreneurs and most citizens do not respect the established laws and mainly the lack of productivity of microentrepreneurs do not generate in them the decision to comply with the planning, tax, labor established. This is reflected in the results of surveys. The workers for their part, due to the lack of employment no choice but to work in inadequate conditions ie without minimum respect for their labor rights and social security. Trujillana Peruvian society are unwilling to comply with the laws established for the best live specifically in this investigation of all Trujillanos.